Educational Philosophy in Islam in The Curriculum Design of Integrated Islamic Education in Malaysia - Raudlatul Firdaus (Jurnal Hikmatuna, 2019)
This article discusses the dichotomy in Islamic education which is the basic problem facing Islamic education today. To overcome these problems, one of them is by organizing an educational model that integrates the science of religion with the knowledge that is based on the philosophy of Islamic education. By employing qualitative method of research, this article strives to identify the philosophy of education in Islam and challenges in the current integrated educational system, which is currently implemented in Malaysian primary and secondary schools. The results of this study, concluded that in overcoming the problem in the preaching of Islamic education, Malaysia implemented integrative Islamic education that integrates religion and science with the Ulul al-Bab model and the KAFFAH curriculum. The concept of Ulul al-Bab is taken from the Qur'an as the basis of the curriculum, while in the KAFFAH curriculum each subject taught is associated with Islamic values and beliefs.